A Proposal to Remove Some Disequilibrating Movements in Official Holdings of Foreign Exchange Reserves - Thorn, Richard S. (The Review of Economics and Statistics, 1962)
I would like to thank Mr. Ball for his thoughtful criticism 1 of my proposal to extend a foreign exchange guarantee to official holdings of foreign exchange and for this opportunity to clarify some points in my original presentation.2 Mr. Ball has levied three general criticisms against my proposal for introducing a multilateral exchange guarantee for official holdings of foreign exchange through the intermediary of the IMF: